Critical appraisal of pralatrexate in the management of difficult-to-treat peripheral T cell lymphoma - Casanova M; Medina-Pérez A; Moreno-Beltran M; Mata-Vazquez M; Rueda A (Dove Medical Press, 2011)
M Casanova, A Medina-Pérez, M Moreno-Beltran, M Mata-Vazquez, A RuedaOncohematology Service, Hospital Costa del Sol, Marbella, SpainAbstract: Aggressive T cell lymphomas are a subgroup of lymphomas with a particularly poor prognosis. This is especially true for patients with recurrent or refractory disease, who typically have limited response to salvage therapy and extremely poor overall survival. For this reason, there is a strong need to develop potentially active drugs for these malignancies. Pralatrexate is a novel antifolate designed to have high affinity for reduced folate carrier type 1. Preclinical and clinical studies have demonstrated that pralatrexate has significant activity against T cell lymphomas. The dose-limiting toxicity for pralatrexate is mucositis, which can be abrogated with folic acid and vitamin B12 supplementation. Pralatrexate is the first single agent approved for the treatment of patients with relapsed or refractory peripheral T cell lymphoma. This approval was based on an overall objective response rate observed in the pivotal study. The overall response rate was 29%, with a median duration of 10.1 months. This article reviews the biochemistry, preclinical experience, metabolism, and pharmacokinetics of pralatrexate, including the clinical experience with this agent in lymphoma. Future areas of development are now focused on identifying synergistic combinations of pralatrexate with other agents and the evaluation of predictive markers for clinical benefit.Keywords: pralatrexate, peripheral T cell lymphoma